A flexible and wearable joint motion sensor using triboelectric nanogenerators for hand gesture monitoring. (21st June 2021) - Sukumaran, Charanya; Viswanathan, Pramila; Munirathinam, Prabavathi; Chandrasekhar, Arunkumar
The rapid advancement in electronic devices and miniaturisation leads to the development of portable and wearable electronic devices for various day-to-day activities. Wearable technology has been rapidly expanding all over the globe due to its flexibility, sensitivity, durability, and multifunctionality as its desirable features. Most of the devices have a higher-end application such as robotics and gesture recognition integrated with artificial intelligence. In this work we propose a Flexion based Triboelectric nanogenerator (F-TENG), which scavenges the mechanical motion of the human finger joints and converts into an electrical signal that can be further programmed using a microcontroller to actuate robotic devices, giving a deeper insight towards self-powered robotic and gesture monitoring applications. The TENG device consists of silicone elastomer as the sensing layer onto which an aluminium electrode is embedded, which enhances the flow of charges between the skin and elastomer and works on the principle of single electrode mode contact electrification. This mode of designing a finger motion sensor is a cost-effective approach, with simple and easy fabrication. The device generates a maximum voltage of 75 V and 9 μA current with high power density. The performance analysis proves that F-TENG can serve as a potential candidate for acquiring the joint signals leading to a world of automation.